If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(k + 5) = -5 Reorder the terms: 3(5 + k) = -5 (5 * 3 + k * 3) = -5 (15 + 3k) = -5 Solving 15 + 3k = -5 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 3k = -5 + -15 Combine like terms: 15 + -15 = 0 0 + 3k = -5 + -15 3k = -5 + -15 Combine like terms: -5 + -15 = -20 3k = -20 Divide each side by '3'. k = -6.666666667 Simplifying k = -6.666666667
| x-7/2=6 | | 2=-4x+6 | | 2=-4x+3 | | 5=x/4-3 | | 3=-6x+9 | | X^2+18x-36=0 | | -3=-6x+9 | | 2X-7=8X+5 | | -2=-4x+6 | | 9x+2y=-7 | | 8p-10=-2p+6 | | -2=4x+9 | | -3=-6x+6 | | 9n-16=6n+5 | | 6x+3-4x-2=8x-6x-2 | | 12-3t=6t-24 | | -21=-18+15 | | 3y=-2(4+3)/2 | | 3y=-2(4+3) | | 2(x+9)=34 | | 5-9= | | y=-2(4+3) | | 4x+2x+3=26 | | 7-54=-43 | | 2b^2=96b | | X^2-8x-11=-2 | | 14=-12x+10 | | 7=-6x+5 | | (5y+13)(4y+29)=0 | | 7x+12y=4 | | -14=-12x+10 | | 4z^2-16z+15=0 |